Switching of a country wide project to a global study ‘IgG4-related disease, pediatric perspective’ - Kaya Akca, Ummusen; Ozen, Seza (Acta Medica, 2025)
IgG4-related disease (IgG4-RD) is a multisystem fibroinflammatory disorder. It has the potential to affect almost any organ, resulting in highly varied clinical presentations. Unlike adults, who often exhibit multiple organ involvement over time, pediatric patients tend to present with localized disease, frequently affecting the orbits. Diagnosing IgG4-RD can be challenging due to its non-specific clinical manifestations and varied organ involvement. Laboratory investigations, histopathological examinations, and radiological assessments provide important information for making the diagnosis. However, the differential is important ruling out conditions such as malignancies, infections, ANCA-associated vasculitis, and sarcoidosis. Laboratory tests, histopathological findings, and radiological evaluations can help to confirm the diagnosis. As for treatment, glucocorticoids (GCs) remain the mainstay of first-line treatment either alone or in combination with immunosuppressants. Nevertheless, recurrence or relapses represent a major problem in the follow-up. The development of multicenter collaborative projects could provide important insights into the diagnosis, treatment, and long-term outcomes of pediatric patients.